The assessment of trapezius muscle symptoms of piano players by the use of infrared thermography - Lourenço da Fonseca, Sofia (2019)
The aim of this study is to understand the correlation of trapezius muscle symptoms in piano players during their performance. The association of piano practice and the general health of a pianist, especially concerning the musculoskeletal system, and head posture has been studied in relation to orofacial anatomic zones and is presumed to have an influence on the biomechanical behavior of the cranio-cervico-mandibular complex (CCMC). Previous research has found that the act of playing piano involves a complex neuromuscular activity with hyperactivity of the masticatory muscles and the postural muscle trapezius. Thermal image assessment was made to the pianist’s CCMC while the piano player was playing his/her piece.